PROBLEMS OF RISK MANAGEMENT IN AGRICULTURAL PRODUCTION - Pejanović, Radovan; NJegomir, Vladimir (Economics of Agriculture, 2011)
Agricultural production is characterised by permanent exposure to variabilities that result from seasonal temperature changes, droughts, floods, policies changes, etc. The aim of the paper is to determine risk exposures in agriculture and methods for risk management in a simplified and holistic way. Research results indicate that all risks can be grouped into regulatory, market and production. The methods of risk management depends on the type of risks. Having considered that risk management is not necessarily directed towards reduction of potential dangers but also towards taking advantage of possible profitable opportunities, understanding and successful application of different alternatives presented in the paper can facilitate the creation of farmers sustainable business success in the long run.